Lentil underground : renegade farmers and the future of food in America - Carlisle, Liz (Gotham Books, 2015)
Forty years ago, corporate agribusiness launched a campaign to push small grain farmers to modernize or perish, or as Nixon's secretary of agriculture Earl Butz put it, "get big or get out." But 27-year-old David Oien decided to take a stand when he dropped out of grad school to return to his family's 280-acre farm, becoming the first in his conservative Montana county to plant a radically different crop: organic lentils. A cheap, healthy source of protein and fiber, lentils are drought-tolerant and don't require irrigation. Unlike the chemically dependent grains American farmers had been told to grow, lentils make their own fertilizer and tolerate variable climate conditions, so their farmers aren't beholden to industrial methods. Today, Oien leads thriving movement of organic farmers who work with heirloom seeds and biologically diverse farm systems. Under the brand Timeless Natural Food, their unique business-cum-movement has grown into a million-dollar enterprise that sells to hundreds of independent natural food stores and a host of renowned restaurants. From the farm belt of red-state America comes this inspiring story of a handful of colorful pioneers who have successfully bucked the chemically-based food chain and the entrenched power of agribusiness's one percent by stubbornly banding together. Journalist and native Montanan Liz Carlisle weaves an eye-opening narrative that will be welcomed by everyone concerned with the future of American agriculture and natural food in an increasingly uncertain world.--From publisher description.